Anti-forensic steganography method based on randomization - Khalaf, Emad Taha; Norrozila, Sulaiman; Mohammed, Muamer N. (Academic World Education & Research Center, 2013)
Information hiding is a technique that embeds secret information into digital contents such as images, audios, movies, documents, etc. This work presents an anti-forensic steganography method that can embed and extract messages from images, which uses the same principle of LSB. The proposed model combines cryptography and steganography. First, the secret information are encrypted using Rijndael Encryption Algorithm. Then, the cover image is divided into several matrices. The number of matrices will be determining by a user, by entering a number, which will also be used to generate a set of random numbers. However, these random numbers will be the index to hiding the encrypted data bits randomly in the least significant bits of pixel channels. This randomization is expected to increase the security of the system as well as the capacity. The metric used for image quality are Peak Signal to Noise Ratio (PSNR) and Correlation Coefficient (Corr). Experimental results show that the proposed method can provide high data security and capacity.